2021
DOI: 10.1038/s41598-021-93494-0
|View full text |Cite
|
Sign up to set email alerts
|

Induced plasticity alters responses to conspecific interactions in seedlings of a perennial grass

Abstract: Plants can interact with different individuals in their lifetime which may lead to plastic response that affect performance. If conspecific interactions are altered through previous plastic responses that could affect stabilizing niche mechanisms, in which conspecifics compete more intensely to promote diversity and coexistence. Here, I show interactions between Pascopyrum smithii and conspecifics resulted in largely canalized traits, whereas P. smithii with an invasive grass, Bromus tectorum resulted in plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Specifically, the proportion of fine roots in P. secunda without cheatgrass competition increased in response to dry conditions, but decreased with cheatgrass competition. This result was unexpected because studies on P. secunda and other native perennial grasses have shown that cheatgrass competition induces greater allocation to root mass and fine roots (Phillips & Leger 2015;Foxx 2021). The trade-off in seedling leaf and root traits makes seed selection for native grass restoration in cheatgrass dominated areas complicated as traits selected for drought tolerance may conflict with traits that resist cheatgrass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the proportion of fine roots in P. secunda without cheatgrass competition increased in response to dry conditions, but decreased with cheatgrass competition. This result was unexpected because studies on P. secunda and other native perennial grasses have shown that cheatgrass competition induces greater allocation to root mass and fine roots (Phillips & Leger 2015;Foxx 2021). The trade-off in seedling leaf and root traits makes seed selection for native grass restoration in cheatgrass dominated areas complicated as traits selected for drought tolerance may conflict with traits that resist cheatgrass.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, native seedlings that germinate later and capitalize on their resource‐conservative traits (finer roots; lower SLA; shorter) further differentiate their niches from invasive species to avoid competition (Gioria & Osborne 2014). There is evidence that native perennial grasses in competition with B. tectorum put greater allocation in root biomass and increase proportion of fine roots (Rowe & Leger 2011; Phillips & Leger 2015; Foxx 2021), but these studies measured traits in one soil moisture condition. When competition effects interact with drought effects, seedling traits may have a trade‐off between growing quickly but costly, and growing slowly but efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…This ability to shift aspects of the phenotype, reversibly or irreversibly, is an essential feature of an organism's ecological interactions and evolution [2]. Plasticity is thought to be involved in mediating processes as diverse as inter-and intraspecific competition [4][5][6][7][8], the evolution of novel traits [9][10][11], speciation and adaptive radiation [12][13][14][15][16][17], and even major transitions in the evolution of individuality and sociality [18].…”
Section: Introductionmentioning
confidence: 99%